2020
DOI: 10.2196/15321
|View full text |Cite|
|
Sign up to set email alerts
|

Functionality of Top-Rated Mobile Apps for Depression: Systematic Search and Evaluation

Abstract: Background In the last decade, there has been a proliferation of mobile apps claiming to support the needs of people living with depression. However, it is unclear what functionality is actually provided by apps for depression, or for whom they are intended. Objective This paper aimed to explore the key features of top-rated apps for depression, including descriptive characteristics, functionality, and ethical concerns, to better inform the design of ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 51 publications
4
57
0
Order By: Relevance
“…However, consumer ratings of health apps are poor indicators of clinical effectiveness and usability, calling into question the value of app ratings altogether (BinDhim et al 2015 ; Gordon et al 2020 ; Singh et al 2016 ). For example, 72% of the 29 most popular depression apps contained no information regarding suicide prevention, and some of these apps contained potentially harmful negative content (Qu et al 2020 ). An additional study of top-ranked depression and smoking cessation apps found that while 92% of apps transmitted user data to third parties, the majority did not clearly disclose this information to users (Huckvale et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, consumer ratings of health apps are poor indicators of clinical effectiveness and usability, calling into question the value of app ratings altogether (BinDhim et al 2015 ; Gordon et al 2020 ; Singh et al 2016 ). For example, 72% of the 29 most popular depression apps contained no information regarding suicide prevention, and some of these apps contained potentially harmful negative content (Qu et al 2020 ). An additional study of top-ranked depression and smoking cessation apps found that while 92% of apps transmitted user data to third parties, the majority did not clearly disclose this information to users (Huckvale et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is concerning, as most MH apps in app stores have little to no empirical backing. Approximately 3% of available depression and anxiety apps provide information regarding testing or effectiveness (Marshall et al 2019;Sucala et al 2017); when restricted to the 29 highest-rated depression apps, this rate only increased to 7% (Qu et al 2020). This has led to the development of multiple online libraries intending to curate effective MH apps (Marshall et al 2019).…”
Section: Skills Knowledge and Resourcesmentioning
confidence: 99%
“…Ethics simply concerns what is good , with a utilitarian perspective dealing with the greatest good for the greatest number of people. To assist in ethical decisions and practices, ethical frameworks outline key concepts such as beneficence and nonmaleficence, justice, responsibility, autonomy, privacy and confidentiality, and respect for the rights and dignity of others [ 13 , 14 , 94 , 95 , 96 , 97 ]. By reflecting on these ethical principles and standards, designers and researchers can ensure that their processes, technological developments, and research are done ethically and for the greater good.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with current standards for app use and functionality indicates that the questions of this database are robust and flexible enough to cover nearly all use cases. A recent exploration of the characteristics, functionality, and ethical concerns of top apps for depression evaluated functionality across three different categories of use—screening, tracking and intervention—that correspond closely with our proposed questions covering various app features 41 . The NICE guidelines propose recommendations for using digital and mobile health interventions among European health systems 42 .…”
Section: Assessing Reliabilitymentioning
confidence: 99%